Case report: Discovery of a de novo FAM111B pathogenic variant in a patient with an APECED-like clinical phenotype - Ferré, Elise M. N.; Yu, Yunting; Oikonomou, Vasileios; Hilfanova, Anna; Lee, Chyi-Chia R.; Rosen, Lindsey B.; Burbelo, Peter D.; Vazquez, Sara E.; Anderson, Mark S.; Barocha, Amisha; Heller, Theo; Soldatos, Ariane; et al. (Frontiers in Immunology, 2023)
Introduction: Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) and poikiloderma in association with tendon contractures, myopathy, and pulmonary fibrosis (POIKTMP) are rare inherited syndromes resulting from biallelic pathogenic variants in AIRE and heterozygous pathogenic variants in FAM111B, respectively. The clinical diagnosis of APECED and POIKTMP rely on the development of two or more characteristic disease manifestations that define the corresponding syndromes. We discuss the shared and distinct clinical, radiographic, and histological features between APECED and POIKTMP presented in our patient case and describe his treatment response to azathioprine for POIKTMP-associated hepatitis, myositis, and pneumonitis. Methods: Through informed consent and enrollment onto IRB-approved protocols (NCT01386437, NCT03206099) the patient underwent a comprehensive clinical evaluation at the NIH Clinical Center alongside exome sequencing, copy number variation analysis, autoantibody surveys, peripheral blood immunophenotyping, and salivary cytokine analyses. Results: We report the presentation and evaluation of a 9-year-old boy who was referred to the NIH Clinical Center with an APECED-like clinical phenotype that included the classic APECED dyad of CMC and hypoparathyroidism. He was found to meet clinical diagnostic criteria for POIKTMP featuring poikiloderma, tendon contractures, myopathy, and pneumonitis, and exome sequencing revealed a de novo c.1292T>C heterozygous pathogenic variant in FAM111B but no deleterious single nucleotide variants or copy number variants in AIRE. Discussion: This report expands upon the available genetic, clinical, autoantibody, immunological, and treatment response information on POIKTMP.